Lithium ion battery
By using a specific proportion of organic solvents and negative adhesives in lithium -ion batteries, the problem of increasing the cycle of lithium -ion battery and storage performance is solved, and better interface protection and bloating performance are achieved, significantly improved the overall performance of the battery Essence
Patent Information
- Application Number
- CN202411342933.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-28
AI Technical Summary
When using non-aqueous electrolyte and negative electrode binder, the circulation and storage performance of existing lithium-ion batteries are difficult to improve. This is mainly due to the poor swelling of the adhesive in the non-aqueous electrolyte, resulting in poor mechanical strength loss and rebound effect.
By introducing circular carbonate solvents, chain carboxylic acid solvents, and fluorosyl ester solvents in the non -hydraulic electrolytes of lithium ion batteries, and using a specific proportion of negative adhesives in the negative active substance layer, it is used. Meet the specific mass percentage content (D/A (A-D) ≤b+C≤2.3 (A+D)) to improve the circulation and storage performance of the battery.
By adjusting the amount of organic solvents and negative adhesives, the protection of the interface of the negative electrode is strengthened, the bloating of the adhesive in the non -hydraulic fluid is improved, the consumption rate of the solvent is reduced, and the circulation and storage performance of the lithium ion battery significantly improves.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field The invention belongs to the technical field of energy storage devices, and in particular relates to a lithium ion battery. Background Art
[0002] Lithium-ion batteries are widely used due to their remarkable characteristics such as high voltage, high capacity and long life. The performance requirements for 3C consumer lithium-ion batteries are becoming more and more stringent. They need to meet both good charging capacity and high energy density and cycle performance. However, from the perspective of the main materials of the battery, further performance improvement has faced many challenges. At present, the binder in the battery assembly plays a vital role in improving the performance of the battery as a necessary additive in the electrode. However, the binder is prone to lose some mechanical strength due to excessive swelling in the non-aqueous electrolyte, and thus cannot achieve a good rebound suppression effect, which is not conducive to the improvement of the cycle performance and storage performance of lithium-ion batteries. Summary of the invention
[0003] Aiming at the problem that the cycle performance and storage performance of the lithium ion battery are difficult to improve due to the combined use of a binder and a non-aqueous electrolyte in the negative electrode of the lithium ion battery in the prior art, a lithium ion battery is provided.
[0004] The technical solution adopted by the present invention to solve the above technical problems is as follows: The present invention provides a lithium ion battery, comprising a non-aqueous electrolyte, a positive electrode and a negative electrode, wherein the non-aqueous electrolyte comprises an organic solvent, a lithium salt and an additive, wherein the organic solvent comprises a cyclic carbonate solvent, a chain carboxylate solvent and a fluoroester solvent, and the negative electrode comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises a negative electrode binder; a is the mass percentage of the negative electrode binder in the negative electrode active material layer; b is the mass percentage of cyclic carbonate solvent in the electrolyte; c is the mass percentage of the chain carboxylic acid ester solvent in the electrolyte; d is the mass percentage of fluorinated ester solvent in the electrolyte; The lithium-ion battery meets the following conditions: d / a(ad)≤b+c≤2.3(a+d).
[0005] Optionally, the sum of the mass percentages of the organic solvent in the non-aqueous electrolyte satisfies the following conditions: b+c+d=100%.
[0006] Optionally, the mass percentage of the binder in the negative electrode active material layer is 0.1%≤a≤5%; The mass percentage of the cyclic carbonate solvent in the non-aqueous electrolyte is 0.1%≤b≤100%; The mass percentage of the chain carboxylic acid ester solvent in the non-aqueous electrolyte is 0.1%≤c≤100%; The mass percentage of the fluorinated ester solvent in the non-aqueous electrolyte is 0.1%≤d≤30%.
[0007] Optionally, the mass percentage of the binder in the negative electrode active material layer is 1%≤a≤2%; The mass percentage of the cyclic carbonate solvent in the non-aqueous electrolyte is 20%≤b≤30%; The mass percentage of the chain carboxylic acid ester solvent in the non-aqueous electrolyte is 50%≤c≤60%; The mass percentage of the fluorinated ester solvent in the non-aqueous electrolyte is 15%≤d≤25%.
[0008] Optionally, the cyclic carbonate solvent includes one or more of ethylene carbonate and propylene carbonate; the chain carboxylate solvent includes one or more of methyl acetate, ethyl acetate, propyl propionate and ethyl propionate; the fluoroester solvent includes one or more of ethyl methyl fluorocarbonate, dimethyl fluorocarbonate, propylene fluorocarbonate, ethyl fluoroacetate and ethylene fluorocarbonate.
[0009] Optionally, the additive includes a polycyclic ester additive, and the polycyclic ester additive is selected from at least one of the following compounds: Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the polycyclic ester additive is 0.5% to 5%.
[0010] Optionally, the additives further include film-forming additives, and the film-forming additives include one or more of sulfonic acid additives, phosphoric acid additives, nitrile additives, vinyl carbonate additives, lithium salt additives and acid anhydride additives.
[0011] Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the film-forming additive is 1% to 5%.
[0012] Optionally, the lithium salt includes one or more of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorobisoxalatophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium difluorophosphate; Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the lithium salt is 10% to 20%.
[0013] Optionally, the negative electrode binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, polyacrylic acid and styrene butadiene rubber.
[0014] The beneficial effects of the present invention are: The lithium ion battery provided by the present invention, the non-aqueous electrolyte includes an organic solvent, the organic solvent includes a cyclic carbonate solvent, a chain carboxylate solvent, and a fluoroester solvent, the negative electrode of the lithium ion battery includes a negative electrode binder, because the cyclic carbonate solvent has a high dielectric constant, it is conducive to the dissolution of lithium salts, thereby promoting the improvement of the cycle performance of the lithium ion battery, but the viscosity of the cyclic carbonate solvent is relatively large under a higher dielectric constant, which limits the migration rate of lithium ions, and the cyclic carbonate solvent is oxidized and produces gas on the positive electrode side, and the negative electrode binder has poor swelling resistance in a single cyclic carbonate solvent, further deteriorating the storage performance. Based on the above reasons, the chain carboxylate solvent and the fluoroester solvent are introduced. After the chain carboxylate solvent and the fluoroester solvent are introduced, the viscosity of the chain carboxylate solvent is relatively low. It helps the migration of lithium ions in the electrolyte, thereby improving the charge and discharge efficiency of the battery. The fluoroester solvent can form a stable solid electrolyte interface film on the electrode surface, effectively inhibiting the decomposition of the electrolyte and the degradation of the electrode material. In addition, the present application finds that the lithium ion battery meets the following conditions by adjusting the ratio of the cyclic carbonate solvent, the chain carboxylic acid ester solvent, the fluoroester solvent and the negative electrode binder in the organic solvent: when d / a(ad)≤b+c≤2.3(a+d), the cycle performance and storage performance of the lithium ion battery have obvious advantages. By adjusting the amount of the organic solvent and the negative electrode binder, the interface protection of the negative electrode can be strengthened, the swelling of the negative electrode binder in the non-aqueous electrolyte can be improved, the consumption rate of the organic solvent can be reduced, and the cycle and storage performance of the lithium ion battery can be further enhanced. DETAILED DESCRIPTION
[0015] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0016] The present invention provides a lithium ion battery, comprising a non-aqueous electrolyte, a positive electrode and a negative electrode, wherein the non-aqueous electrolyte comprises an organic solvent, a lithium salt and an additive, wherein the organic solvent comprises a cyclic carbonate solvent, a chain carboxylate solvent and a fluoroester solvent, and the negative electrode comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises a negative electrode binder; a is the mass percentage of the negative electrode binder in the negative electrode active material layer; b is the mass percentage of cyclic carbonate solvent in the electrolyte; c is the mass percentage of the chain carboxylic acid ester solvent in the electrolyte; d is the mass percentage of fluorinated ester solvent in the electrolyte; The lithium-ion battery meets the following conditions: d / a(ad)≤b+c≤2.3(a+d).
[0017] The lithium ion battery provided by the present invention comprises a non-aqueous electrolyte comprising an organic solvent, wherein the organic solvent comprises a cyclic carbonate solvent, a chain carboxylate solvent, and a fluoroester solvent. The negative electrode of the lithium ion battery comprises a negative electrode binder. Since the cyclic carbonate solvent has a high dielectric constant, it is conducive to the dissolution of lithium salts, thereby promoting the improvement of the cycle performance of the lithium ion battery. However, the viscosity of the cyclic carbonate solvent is relatively large under a relatively high dielectric constant, which limits the migration rate of lithium ions. In addition, the cyclic carbonate solvent is oxidized and produces gas on the positive electrode side. The negative electrode binder has poor swelling resistance in a single cyclic carbonate solvent, further deteriorating the storage performance. Based on the above reasons, the chain carboxylate solvent and the fluoroester solvent are introduced. After the chain carboxylate solvent and the fluoroester solvent are introduced, the viscosity of the chain carboxylate solvent is relatively low, which is conducive to the migration of lithium ions in the electrolyte, thereby improving the charge and discharge efficiency of the battery. The fluoroester solvent can form a stable solid electrolyte interface film on the electrode surface. Effectively inhibit the decomposition of the electrolyte and the degradation of the electrode material; in addition, the present application finds that by adjusting the ratio between the cyclic carbonate solvent, the chain carboxylic ester solvent, the fluoroester solvent and the negative electrode binder in the organic solvent, when only b+c≤2.3(a+d) is satisfied, only the high temperature cycle performance of the lithium ion battery is improved, and its high temperature storage performance is not significantly improved. When only b+c≥d / a(ad) is satisfied, the cycle performance of the lithium ion battery has no obvious advantage. However, when the ratio between the cyclic carbonate solvent, the chain carboxylic ester solvent, the fluoroester solvent and the negative electrode binder in the organic solvent satisfies d / a(ad)≤b+c≤2.3(a+d), the cycle performance and storage performance of the lithium ion battery have obvious advantages. By adjusting the amount of the organic solvent and the negative electrode binder, the interface protection of the negative electrode can be strengthened, the swelling of the negative electrode binder in the non-aqueous electrolyte can be improved, the consumption rate of the organic solvent can be reduced, and the cycle and storage performance of the lithium ion battery can be further enhanced.
[0018] In one embodiment, the lithium-ion battery meets the following conditions: The sum of the mass percentages of the organic solvents in the non-aqueous electrolyte satisfies the following conditions: b+c+d=100%.
[0019] Specifically, when the sum of the mass percentages of the organic solvent in the non-aqueous electrolyte satisfies b+c+d=100%, the cycle performance and storage performance of the lithium-ion battery have obvious advantages. By adjusting the amount of the organic solvent and the negative electrode binder, the interface protection of the negative electrode can be enhanced, the swelling of the negative electrode binder in the non-aqueous electrolyte can be improved, the consumption rate of the organic solvent can be reduced, and the cycle and storage performance of the lithium-ion battery can be further enhanced.
[0020] In one embodiment, the mass percentage of the binder in the negative electrode active material layer is 0.1%≤a≤5%; The mass percentage of the cyclic carbonate solvent in the non-aqueous electrolyte is 0.1%≤b≤100%; The mass percentage of the chain carboxylic acid ester solvent in the non-aqueous electrolyte is 0.1%≤c≤100%; The mass percentage of the fluorinated ester solvent in the non-aqueous electrolyte is 0.1%≤d≤30%.
[0021] In a specific embodiment, the mass percentage of the binder in the negative electrode active material layer can be 0.1%, 0.8%, 1.0%, 1.3%, 1.5%, 1.8%, 2.0%, 2.3%, 2.7%, 3.0%, 3.5%, 4.0%, 4.5% or 5.0%; the mass percentage of the cyclic carbonate solvent can be 0.1%, 15%, 20%, 23%, 25%, 28%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 80%, 90%, 95% or 100%; the mass percentage of the linear carboxylate solvent can be 0.1%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 52%, 55%, 58%, 60%, 65%, 70%, 80%, 90%, 95% or 100%; the mass percentage of the fluoroester solvent can be 0.1%, 1.0%, 3.0%, 5.0%, 8.0%, 10%, 13%, 15%, 18%, 20%, 23%, 25% or 30%.
[0022] In one embodiment, the mass percentage of the binder in the negative electrode active material layer is 1%≤a≤2%; The mass percentage of the cyclic carbonate solvent in the non-aqueous electrolyte is 20%≤b≤30%; The mass percentage of the chain carboxylic acid ester solvent in the non-aqueous electrolyte is 50%≤c≤60%; The mass percentage of the fluorinated ester solvent in the non-aqueous electrolyte is 15%≤d≤25%.
[0023] In one embodiment, the cyclic carbonate solvent includes one or more of ethylene carbonate and propylene carbonate; the chain carboxylate solvent includes one or more of methyl acetate, ethyl acetate, propyl propionate and ethyl propionate; the fluoroester solvent includes one or more of ethyl methyl fluorocarbonate, dimethyl fluorocarbonate, propylene fluorocarbonate, ethyl fluoroacetate and ethylene fluorocarbonate.
[0024] Specifically, the cyclic carbonate solvent has a higher dielectric constant, can effectively dissolve lithium salts, and enhance the ionic conductivity of the electrolyte; the fluoroester solvent has stronger oxidation resistance and higher flash point, effectively improves the thermal stability and safety of the electrolyte, and the fluoroester solvent can improve the wettability between the electrolyte and the electrode material, which helps to form a more uniform and stable SEI film, reduce side reactions, and extend the battery life; the chain carboxylate solvent has a lower viscosity, which helps the migration of lithium ions in the electrolyte and improves the charge and discharge efficiency. In addition, this type of solvent has excellent electrochemical stability and can effectively inhibit the decomposition of the electrolyte and the degradation of the electrode material; in a preferred embodiment of the present application, the cyclic carbonate solvent is selected from one or both of ethylene carbonate (EC) and propylene carbonate (PC), the chain carboxylate solvent is selected from one or both of ethyl propionate (EP) and propyl propionate (PP), and the fluoroester solvent is selected from one or both of ethyl fluoroacetate (DFEA) and fluoroethylene carbonate (FEC).
[0025] In one embodiment, the additive comprises a polycyclic ester additive, and the polycyclic ester additive is selected from at least one of the following compounds: Specifically, the polycyclic ester additive participates in film formation on the negative electrode surface. The interface film can effectively increase the mobility of lithium ions during the high-temperature cycle of the battery, and at the same time has a good protective effect on the electrode material, reduces the redox reaction between the electrolyte and the electrode material, inhibits the negative electrode interface side reaction, and improves the high-temperature performance and safety performance of the lithium-ion battery.
[0026] In one embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the polycyclic ester additive is 0.5%-5%.
[0027] Specifically, the mass percentage of the polycyclic ester additive can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%. In a preferred embodiment, the mass percentage of the polycyclic ester additive is 1% to 3%.
[0028] In one embodiment, the additive further includes a film-forming additive, and the film-forming additive includes one or more of a sulfonic acid additive, a phosphoric acid additive, a nitrile additive, a vinyl carbonate additive, a lithium salt additive, and an anhydride additive.
[0029] Specifically, the sulfonic acid additive is selected from at least one of 1,3-propane sultone, 1,4-butane sultone, and 1,3-propylene sultone; the phosphoric acid additive is selected from at least one of tris(trimethylsilane) phosphate and tris(trimethylsilane) phosphite; the nitrile additive is selected from at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, and sebacate; the ethylene carbonate additive is selected from ethylene carbonate (VC); in a preferred embodiment, the film-forming additive is selected from any one or more of 1,3-propane sultone (PS), 1,3,6-hexanetrinitrile (HTCN), succinonitrile (SN) and ethylene carbonate (VC).
[0030] In one embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the film-forming additive is 1%-5%.
[0031] In one embodiment, the lithium salt includes one or more of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorobisoxalatophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium difluorophosphate.
[0032] Specifically, in a preferred embodiment, the lithium salt is selected from lithium hexafluorophosphate (LiPF6). If the lithium salt concentration is too low, it will affect the conductivity of the electrolyte and reduce the rate and cycle performance of the entire battery system. If the lithium salt concentration is too high, the viscosity of the electrolyte is too large, which also affects the rate of the battery system. Therefore, when preparing lithium-ion batteries, it is necessary to select an appropriate lithium salt concentration.
[0033] In one embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the lithium salt is 10%-20%.
[0034] In one embodiment, the negative electrode binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, polyacrylic acid and styrene butadiene rubber.
[0035] Specifically, in a preferred embodiment, the negative electrode binder includes at least one of SBR and PAA.
[0036] The present invention is further described below by way of examples.
[0037] Table 1 Preparation of different types of negative electrodes: The negative electrode active material silicon carbon particles, graphite, conductive agent SP, thickener CMC, and binder SBR / PAA are mixed according to the mass ratios in Table 1, and are fully stirred and mixed in an appropriate amount of deionized water solvent to form a uniform negative electrode slurry for forming a negative electrode active material layer. The negative electrode slurry is coated on the negative electrode current collector Cu foil, and different types of negative electrodes that meet the winding requirements are made through processes such as drying, cold pressing, slitting, sheeting, welding, and ear gluing.
[0038] Table 2 Preparation of different types of electrolyte: In an argon environment with a water content of <10ppm, the organic solvents shown in Table 2 and their corresponding mass percentages were added, and after mixing, 14.4wt.% LiPF6, 1wt.% VC, 3wt.% PS, 1wt.% SN and 2wt.% HTCN were added.
[0039] Table 3 Continue Table 3 Continue Table 3 Continue Table 3 Example 1 This embodiment is used to illustrate the lithium ion battery disclosed in the present invention, including the following operations: Preparation of positive electrode: The positive electrode active material lithium cobalt oxide (LCO), the conductive agent CNT, and the adhesive PVDF are fully stirred and mixed in NMP solvent at a weight ratio of 97:1.5:1.5, and the slurry is coated on an aluminum foil with a safety primer. After drying, cold pressing, slitting, sheeting, welding, and lug gluing, a positive electrode that meets the winding requirements is made; The negative electrode sheet model is selected from a-1, and the non-aqueous electrolyte is selected from EL-3, wherein b+c=0.7, 2.3(a+d)=0.759, d / a(ad)=0.027, satisfying d / a(ad)≤b+c≤2.3(a+d).
[0040] Embodiments 2 to 44 Examples 2 to 44 are used to illustrate the lithium ion battery disclosed in the present invention, and include most of the operations of Example 1, except that: The models of the negative electrode and the non-aqueous electrolyte and the relationships they satisfy are as shown in Table 3.
[0041] Embodiments 45 to 51 Examples 45 to 51 are used to illustrate the lithium ion battery disclosed in the present invention, and include most of the operations of Example 1, except that: The negative electrode, the model of the non-aqueous electrolyte, the type of the polycyclic ester additive, the amount of the polycyclic ester additive added, and the relationship they satisfy are as shown in Table 3.
[0042] Comparative Examples 1 to 31 Comparative Examples 1 to 31 are used to compare and illustrate the lithium ion batteries disclosed in the present invention, including most of the operations of Example 1, except that: The models of the negative electrode and the non-aqueous electrolyte and the relationships they satisfy are as shown in Table 3.
[0043] Performance Testing The following performance tests were performed on Examples 1 to 51 and Comparative Examples 1 to 31 prepared as above: Lithium-ion battery performance test 25℃ cycle test: charge to 4.53V at 1C constant current at 25℃, cut-off current 0.05C, stand for 10min, test initial internal resistance R0, full charge thickness and charging capacity, discharge to 3.0V at 0.5C, record discharge capacity C0 as the initial, repeat 600 cycles, and get capacity C600, internal resistance R600, thickness D600 after 600 cycles. The first coulomb efficiency = C0 discharge / C0 charge, capacity retention rate = C600 / C0, internal resistance growth rate = R600 / R0-1, thickness change rate = D600 / D0-1.
[0044] 45℃ cycle test: charge to 4.53V at 1C constant current at 45℃, cut-off current 0.05C, stand for 10min, test initial internal resistance R0, full charge thickness and charging capacity, discharge to 3.0V at 0.5C, record discharge capacity C0 as initial, repeat 200 times, and get capacity C200, internal resistance R200, thickness D200 after 200 cycles. The first coulomb efficiency = C0 discharge / C0 charge, capacity retention rate = C200 / C0, internal resistance growth rate = R200 / R0-1, thickness change rate = D200 / D0-1.
[0045] 0.5C charge to 4.53V, 0.05C cut-off, stand for 10min, test initial thickness voltage internal resistance (normal temperature test), 0.2C discharge to 2.8V as initial; (normal temperature test), 0.5C charge to 4.53V, 0.05C cut-off, stand for 10min, fully charged battery stored at 60℃, 30D test thickness, internal resistance, voltage, internal resistance growth rate = R30 / R0-1, thickness change rate = D30 / D0-1 The test results obtained are entered in Table 4.
[0046] Table 4 Continued from Table 4 Continued from Table 4 It can be seen from the test results in Table 4 that the test results of Examples 1 to 51 are better than those of Comparative Examples 1 to 31; the cycle performance of the lithium ion batteries prepared in Comparative Examples 1 to 27 is poor, because the ratio of the cyclic carbonate solvent, the chain carboxylate solvent, the fluoroester solvent in the non-aqueous electrolyte of the lithium ion batteries prepared in Comparative Examples 1 to 27 and the negative electrode binder in the negative electrode active material layer only satisfies b+c≥d / a(ad). Further research has found that when b+c≥d / a(ad) is satisfied, after the chain carboxylate solvent and the fluoroester solvent are introduced, the oxidation resistance of the solvent is enhanced and the film formation stability of the positive and negative electrodes is enhanced, the film formation of the positive and negative electrodes hinders the bonding of the negative electrode and the contact with the solvent, the lithium ion transmission path becomes longer, and the cycle life is shortened; Comparative Examples 28 to 31 satisfy b+c≤2.3(a+d), and the high temperature cycle performance of the lithium ion battery is improved, but the storage performance is deteriorated. This is because the introduction of a high dielectric constant solvent is conducive to the dissolution of the lithium salt, the cycle performance is improved, but the lithium ion migration rate is reduced, and the cyclic carbonate is oxidized and produces gas on the positive electrode side. Secondly, the negative electrode binder PAA has poor swelling resistance in a single cyclic carbonate, which further deteriorates the storage performance; Examples 1 to 51 simultaneously satisfy d / a(ad)≤b+c≤2.3(a+d). From the test results, they have obvious advantages in improving the cycle performance and storage performance of lithium-ion batteries. That is, by adjusting the amount of electrolyte solvent and negative electrode binder, the interface protection of the negative electrode can be enhanced, the consumption rate of the solvent can be reduced, and the cycle and storage performance of the lithium-ion battery can be further improved. Compared with Examples 1 to 44, Examples 45 to 51, on the basis of satisfying d / a(ad)≤b+c≤2.3(a+d), additionally add the polycyclic ester additive described in the present application to the non-aqueous electrolyte, the cycle performance of the lithium ion battery is further improved, and the expansion rate is suppressed. This is because the polycyclic ester additive participates in the surface film formation of the negative electrode, and the preferential negative electrode film formation reduces the redox reaction between the electrolyte and the electrode material. At the same time, the interface film can effectively increase the movement speed of lithium ions during the high-temperature cycle of the battery, thereby improving the high-temperature cycle performance and safety performance of the lithium ion battery. In summary, in the lithium ion battery described in the present application, when the non-aqueous electrolyte satisfies d / a(ad)≤b+c≤2.3(a+d), the electrolyte can take into account the liquid retention of the battery cell and the mechanical strength of the binder, improve the cycle and storage performance of the electrochemical device, and at the same time, after further introducing the polycyclic ester additive, the polycyclic ester additive participates in the surface film formation of the negative electrode, suppresses the negative electrode interface side reactions, and improves the high temperature performance and safety of the lithium ion battery.
[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: The invention comprises a non-aqueous electrolyte, a positive electrode and a negative electrode, wherein the non-aqueous electrolyte comprises an organic solvent, a lithium salt and an additive, the organic solvent comprises a cyclic carbonate solvent, a chain carboxylate solvent and a fluorinated ester solvent, the negative electrode comprises a negative electrode active material layer, and the negative electrode active material layer comprises a negative electrode binder; a is the mass percentage of the negative electrode binder in the negative electrode active material layer; b is the mass percentage of cyclic carbonate solvent in the electrolyte; c is the mass percentage of the chain carboxylic acid ester solvent in the electrolyte; d is the mass percentage of fluorinated ester solvent in the electrolyte; The lithium-ion battery meets the following conditions: d / a(ad)≤b+c≤2.3(a+d).
2. A lithium ion battery according to claim 1, characterized in that: The sum of the mass percentages of the organic solvent in the non-aqueous electrolyte satisfies the following conditions: b+c+d=100%.
3. A lithium ion battery according to claim 1, characterized in that: The mass percentage of the binder in the negative electrode active material layer is 0.1%≤a≤5%; The mass percentage of the cyclic carbonate solvent in the non-aqueous electrolyte is 0.1%≤b≤100%; The mass percentage of the chain carboxylic acid ester solvent in the non-aqueous electrolyte is 0.1%≤c≤100%; The mass percentage of the fluorinated ester solvent in the non-aqueous electrolyte is 0.1%≤d≤30%.
4. A lithium ion battery according to claim 1, characterized in that: The mass percentage of the binder in the negative electrode active material layer is 1%≤a≤2%; The mass percentage of the cyclic carbonate solvent in the non-aqueous electrolyte is 20%≤b≤30%; The mass percentage of the chain carboxylic acid ester solvent in the non-aqueous electrolyte is 50%≤c≤60%; The mass percentage of the fluorinated ester solvent in the non-aqueous electrolyte is 15%≤d≤25%.
5. A lithium ion battery according to claim 1, characterized in that: The cyclic carbonate solvent includes one or more of ethylene carbonate and propylene carbonate; the chain carboxylate solvent includes one or more of methyl acetate, ethyl acetate, propyl propionate and ethyl propionate; the fluoroester solvent includes one or more of ethyl methyl fluorocarbonate, dimethyl fluorocarbonate, propylene fluorocarbonate, ethyl fluoroacetate and ethylene fluorocarbonate.
6. A lithium ion battery according to claim 1, characterized in that: The additive comprises a polycyclic ester additive, and the polycyclic ester additive is selected from at least one of the following compounds: 。 7. A lithium ion battery according to claim 6, characterized in that: Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the polycyclic ester additive is 0.5% to 5%.
8. A lithium ion battery according to claim 1, characterized in that: The additives also include film-forming additives, which include one or more of sulfonic acid additives, phosphoric acid additives, nitrile additives, vinyl carbonate additives, lithium salt additives and acid anhydride additives; based on the total mass of the non-aqueous electrolyte as 100%, the mass percentage of the film-forming additive is 1%~5%.
9. A lithium ion battery according to claim 1, characterized in that: The lithium salt includes one or more of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorobisoxalatophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium difluorophosphate; Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the lithium salt is 10% to 20%.
10. A lithium ion battery according to claim 1, characterized in that: The negative electrode binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, polyacrylic acid and styrene butadiene rubber.